The Differences in Understanding of Students in the Mountains and the Coast in Recognizing the Types of Insects - Endro Tri Susdarwono (Mafapress bekerja sama dengan Prodi PGMI Fakultas Tarbiyah IPMAFA Pati, 2022)
This study aims to provide a description of how elementary school students in grade 2 recognize the types of insects through their existence in the nature around us. The method used in this research is semi-experimental research, the characteristics of experimental research in this study include manipulation and observation. Samples were taken from two populations, namely: elementary school students in mountainous areas and elementary school students in coastal areas. The research question is whether there are differences in understanding related to the material for elementary school students in mountainous and coastal areas? Based on the comparison between the D value in the table and the calculated D value, the D value is 0.216667. This value is smaller than the D value in the table of 0.582317. Thus the null hypothesis is declared rejected, while the alternative hypothesis is declared accepted. In this condition, it can be concluded that the level of understanding of material related to insects through their existence around us, there is a difference in understanding between elementary school students who are in mountainous locations or areas and elementary school students who are in coastal locations or areas.